Tinjauan Yuridis Pelanggaran HAM Berat Terhadap Korban Sipil dalam Invasi Rusia ke Ukraina - Azizi, Umar Mochtar; Alfiansyah; Chaidir, Mega Fadhillah; Donri, Wahyu (Jurnal Panorama Hukum, 2022)
Human Rights are rights that are inherent in human beings. However, when there is an armed conflict between countries, human rights are often ignored. This study aims to identify and examine cases of gross human rights violations committed by Russia against Ukraine. The research method used is a normative juridical research method, where the research focuses on the study of the rules or norms in positive law. So that based on international law in general the protection of the Ukrainian people is stated in international rules or instruments such as the Universal Declaration of Human Rights, International Humanitarian Law, Geneva Law, the Covenant on Civil and Political Rights, the Law of Armed Conflict (LOAC)